Exploratory research on sports facilities construction in Malaysia - Barghchi, Maassoumeh; Omar, Dasimah; Aman, Mohd Salleh; Kazemian, Sina; Kim Huat, Bujang (American-Eurasian Network for Scientific Information, 2010)
Sports and sports facilities development have improved rapidly over the past years in Malaysia. However, such improvements are inadequate compared to the overall development of sports at international level. In recent years sport is getting more and more influential and it will continue to grow in importance, even for developing countries. Recent developments have witnessed the use of sports facilities as a force for urban growth. The aim of this research is to examine the relationship between sports facilities and urban development in Malaysia. The study uses the expert opinion of town planners, as key players in decision making, working in the specific government's agencies either in Kuala Lumpur or all 13 states, who are responsible for formulating and administrating all national policies relating to town and country planning. The paper argues that simultaneously with emphasis on creating a sports culture among Malaysian, there is a need for a new perspective and a new approach for sports facilities development in the future. In addition, further investigation on the impacts of sports facilities might help to improve the effectiveness and contribution of sports facilities to urban development.